Comprehensive study for radiation shielding features for Bi2O3–B2O3–ZnO composite using computational radioanalytical Phy-X/PSD, MCNP5, and SRIM software - Y. S. Alajerami; M. H. A. Mhareb; M. I. Sayyed; M. Kh. Hamad; F. Kodeh; M. Rashad; M. Mitwalli (Scientific Reports)
Abstract The current study uses zinc oxide doping nanoparticles to investigate the radiation shielding properties of bismuth borate glass. Fourier transform infrared (FTIR) and X-ray diffraction (XRD) examined the structural characteristics of the current samples. In contrast, the optical properties were determined based on the absorption spectrum for current samples. Appraisal studies are carried out depending on the simulation capabilities of Phy-X/PSD software in conjunction with MCNP5 to achieve this goal. In addition, the neutron and charged particle shielding properties were evaluated theoretically. All glasses are amorphous, as confirmed by the XRD data, and the FTIR data showed several vibration bands and functional groups. The density showed rising from 5.981 to 6.433 g/cm3 with adding ZnO. The band gap values reduced from 2.831 to 2.091 eV for direct and 3.024 to 2.218 eV for indirect with adding ZnO. The investigations' findings demonstrate a strong agreement between the theoretical and simulation-derived estimates of the mass attenuation coefficient. The relative difference of MAC results lie in the range 0.106–2.941% for BBZ0, 0.105–4.348% for BBZ1, 0.105–3.398% for BBZ2, and 0.105–2.032% for BBZ3. The study's findings are valuable insights from thoroughly examining these parameters, which can potentially improve the radiation protection abilities of Bi2O3–B2O3–ZnO glasses. This study represents a significant step in developing more efficient and safer materials for gamma radiation shielding applications.